Latent Myofascial Trigger Points Injection Reduced the Severity of Persistent, Moderate to Severe Allergic Rhinitis: A Randomized Controlled Trial - Liu, Yu; Yang, Yan; Hu, Qiya; Badughaish, Ahmed; Zhang, Hanbing; Qi, Feng; Hou, Yuedong (Frontiers in Medicine, 2021)
Background: Myofascial trigger points (MTrPs) injection has been effectively used for the management of chronic painful diseases. Latent MTrPs can induce autonomic nerve phenomena. In our clinic, we observed that AR symptoms significantly improved when latent MTrPs injection was performed for migraine. Objective: To compare the efficacy and safety between latent MTrPs injection and sublingual immunotherapy (SLIT) in paitients with persistent, moderate to severe AR. Methods: This randomized controlled trial enrolled 112 patients with AR was conducted. Patients randomized to receive sublingual immunotherapy (SLIT,n = 56) or latent MTrPs injection. Total nasal symptom score (TNSS, n = 56), nasal symptoms, medication days and adverse events were evaluated during the 9 months follow-up period after treatment in both groups. Results: Latent MTrPs injection significantly reduced TNSS to a greater level from baseline (from 8.36 ± 1.96 to 4.43 ± 2.18) than SLIT (from 8.66 ± 2.31 to 7.80 ± 2.47) at the week 1 (P < 0.001), and sustained the improvement in symptoms throughout to the month 9. Latent MTrPs showed statistically significant differences vs. SLIT for the TNSS reduction both at month 2 (6.59 ± 2.37 vs. 2.64 ± 2.38; p < 0.001) and month 3 (4.59 ± 2.77 vs. 2.62 ± 2.43; p < 0.001). Latent MTrPs also showed a better improvent in the onset time of efficacy compared with SLIT. Adverse reactions were few and non-serious in both treatment groups. Conclusions: Latent MTrPs injection significantly improved symptoms and decreased symptom-relieving medication use in patients with AR and was well tolerated.